2019
DOI: 10.1016/j.compchemeng.2019.05.033
|View full text |Cite
|
Sign up to set email alerts
|

A scalable stochastic programming approach for the design of flexible systems

Abstract: We study the problem of designing systems in order to minimize cost while meeting a given flexibility target. Flexibility is attained by enforcing a joint chance constraint, which ensures that the system will exhibit feasible operation with a given target probability level. Unfortunately, joint chance constraints are complicated mathematical objects that often need to be reformulated using mixed-integer programming (MIP) techniques. In this work, we cast the design problem as a conflict resolution problem that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This problem is fully decoupled in the MC samples k ∈ K and, thus, can be trivially parallelized. It has been recently reported that a continuous relaxation of this problem (in combination with an appropriate rounding strategy) provides high-quality approximations of the exact solution (Pulsipher and Zavala 2019). Specifically, we can relax y k ∈ {0, 1} to 0 ≤ y k ≤ 1 and then round the optimized relaxed y k * values to 1 if they are nonzero.…”
Section: Computing the Reliability Measurementioning
confidence: 99%
See 1 more Smart Citation
“…This problem is fully decoupled in the MC samples k ∈ K and, thus, can be trivially parallelized. It has been recently reported that a continuous relaxation of this problem (in combination with an appropriate rounding strategy) provides high-quality approximations of the exact solution (Pulsipher and Zavala 2019). Specifically, we can relax y k ∈ {0, 1} to 0 ≤ y k ≤ 1 and then round the optimized relaxed y k * values to 1 if they are nonzero.…”
Section: Computing the Reliability Measurementioning
confidence: 99%
“…We observe that 5 out of 6 pairs are exactly recovered and a pair is underestimated. In Pulsipher and Zavala (2019) it is hypothesized that the quality of the approximations is the result of degeneracy associated with the joint chance constraint (i.e., multiple solutions yield the same optimal value). This simple network exhibits little degeneracy at that solution because its solution space is small.…”
Section: Continuous Approximation For Design Problemmentioning
confidence: 99%